New Orchids from Vietnam - Averyanov, L. V.; Efimov, P. G. (Rheedea, 2006)
Seven new species of orchids viz.: Calanthe duyana, Dendrobium chapaense, Epipactis alatus, Gastrodia major , G. punctata, Platanthera epiphytica and Zeuxine bidupensis discovered recently from Vietnam are described with illustrations. Their morphological characters that make them taxonomically distinct from their respective most allied species are highlighted.